Identifying gaps in care upon discharge from inpatient psychiatry settings to the community - Kapty, Connor (My University, 2025)
This literature review examines gaps in care within healthcare systems that negatively impact service users as they transition from inpatient psychiatric settings to community settings. Topics such as historical contexts, readmission rates, intrapersonal factors, and institutional limitations are taken into account to explain the complex relationship between community and inpatient psychiatric services and how they influence current gaps in care. Interventions to address these limitations are explored, which is aimed at examining different models of care and their subsequent impact on gaps in care. In these interventions, concepts such as continuity of care and therapeutic relationships are then proposed as vital factors when addressing gaps in care. Finally, this literature review suggests areas for future research to improve upon gaps in care.
Keywords: healthcare systems; inpatient psychiatric settings; community settings; gaps in care